New band structures in ~（107）Ag - 张彪 竺礼华 孙慧斌 贺创业 吴晓光 陆景彬 马英君 郝昕 郑云 于蓓蓓 李广生 姚顺和 王烈林 徐川 王建国 顾龙 (Chinese physics C, 2011)
High spin states in 107Ag are studied via the 100Mo（11B,4n） 107Ag reaction at an incident beam energy of 60 MeV. Prompt γ-γ coincidence and DCO ratios are measured by the detector arrays in CIAE. The level scheme has been updated and a new negative band belonging to 107 Ag is identified. The new negative side band has been constructed and its configuration is tentatively assigned to πg9/2νh11/2（g7/2/d5/2）.